Reproductive performances of wild male tiger shrimp Penaeus monodon post-injection of oocyte developer without eyestalk ablation - Prasetyo, Dony; Laining, Asda; Sudrajat, Agus Oman (Indonesian Society of Scientific Aquaculture (ISSA), 2017)
ABSTRACT The aim of this study was to evaluate the effect of oodev on the gonadal maturation and characteristic of spermatophore and spermatozoa produced by the wild male black tiger shrimp against eyestalk ablation. The treatments were two doses of oodev injection at 0.5 (OD0.5) and 1 (OD1.0) mL/kg of body weight and a control was eyestalk ablation (AB). The male stock of tiger shrimp used was from wild with body weight ranged from 55‒85 g, stocked into three of 10 tonnages concrete tanks with density of 25 males/tank. Oodev injection was applied for two times with one week interval. Tiger shrimp of OD0.5 group produced the highest number of gonadal maturing which was 84% followed by AB (68%) and OD1.0 (64%). Oodev injection was able to shorten the time required for spermatophore maturation at maturation phase which happened simultaneously within 7 days post injection compared to that of ablated males. Positive correlation (R2=0.612) was detected between the shrimp weight and weight of spermatophore of the tiger shrimp while correlation between spermatophore weight and number of spermatozoa was relatively low (R2=0.415). Total fatty acid tented to be higher in males injected with oodev compared to ablated males. Concentration of arachidonic acid in the muscle of male stock in OD1.0 group was extremely low of 0.0037% of total lipid compared to AB (0.3190%) and OD0.5 (0.2806%). Oodev injection at the dose of 0.5 mL/kg of tiger shrimp could improve the number of males stock producing spermatophore compared to eyestalk ablation. Simultaneously matured-spermatophore of wild male tiger shrimp within short time could be achieved through oodev injection. Keywords: oodev, spermatophore, reproduction, tiger shrimp ABSTRAK Tujuan penelitian ini adalah mengevaluasi efek hormon oodev terhadap pematangan gonad dan karakter spermatofor dan spermatozoa yang dihasilkan oleh induk udang windu jantan alam dibandingkan dengan teknik ablasi tangkai mata. Perlakuan yang dicobakan adalah dua dosis injeksi oodev yaitu 0,5 (OD0,5) dan 1 (OD1.0) mL/kg bobot tubuh dan kontrol yaitu ablasi tangkai mata. Induk udang windu jantan yang digunakan berasal dari alam berbobot antara 55‒85 g, ditebar dalam tiga bak pematangan gonad berkapasitas 10 ton dengan kepadatan 25 ekor/bak. Injeksi oodev dilakukan dua kali dengan interval satu minggu. Induk udang windu pada OD0,5 menghasilkan jumlah induk matang gonad tertinggi yaitu 84%, diikuti oleh AB (68%) dan OD1 (64%). Injeksi oodev mampu mempersingkat masa pematangan spermatofor pada fase maturasi dan pematangan tersebut terjadi secara simultan setelah 7 hari pascainjeksi dibandingkan dengan induk yang di ablasi. Korelasi positif (R2=0,612) dideteksi antara bobot tubuh dan bobot spermatofor induk udang windu, sedangkan korelasi antara bobot spermatofor dan jumlah spermatozoa relatif lemah (R2=0,415). Total asam lemak daging cenderung lebih besar pada induk udang windu jantan yang diinjeksi oodev dibandingkan yang diablasi. Konsentrasi arachidonic acid dalam daging induk yang diinjeksi OD1 sangat rendah sebesar 0,0037% dari lemak dibandingkan AB (0,3190%) dan OD0,5 (0,2806%). Injeksi oodev pada dosis 0,5 mL/kg udang windu dapat meningkatkan jumlah induk yang menghasilkan spermatofor dibandingkan ablasi tangkai mata. Pematangan gonad udang windu jantan alam secara simultan dan singkat dapat dilakukan melalui injeksi oodev. Kata kunci: oodev, spermatofor, reproduksi, udang windu